2022
DOI: 10.1155/2022/7830126
|View full text |Cite
|
Sign up to set email alerts
|

Rhodotorula mucilaginosa Fungemia, a Rare Opportunistic Infection without Central Venous Catheter Implantation, Successfully Treated by Liposomal Amphotericin B

Abstract: Background. Fungemia due to Rhodotorula mucilaginosa is rare and highly resistance to antifungal therapy. Since most cases of R. mucilaginosa fungemia are attributed to medical devices, limited information is currently available on infection without central venous catheter (CVC) implantation. We herein report a case of R. mucilaginosa fungemia without implantation of CVC, successfully treated by liposomal amphotericin B (L-AMB). Case Presentation. An 81-year-old man with a history of chronic obstructive lung d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…However, the other antifungals, azoles (fluconazole, itraconazole, posaconazole, voriconazole), and echinocandins (anidulafungin, caspofungin) showed high MICs, indicating poor response to treatment (Table 1). Another case of Rhotodorula mucilaginosa fungaemia reported in literature showed that the MIC was comparable with our finding with amphotericin B and fluconazole was 0.25 μg/mL and 128 μg/mL respectively [5]. Clinically, this was evident when the patient's condition did not improve despite adequate dosing and duration of fluconazole during the initial treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the other antifungals, azoles (fluconazole, itraconazole, posaconazole, voriconazole), and echinocandins (anidulafungin, caspofungin) showed high MICs, indicating poor response to treatment (Table 1). Another case of Rhotodorula mucilaginosa fungaemia reported in literature showed that the MIC was comparable with our finding with amphotericin B and fluconazole was 0.25 μg/mL and 128 μg/mL respectively [5]. Clinically, this was evident when the patient's condition did not improve despite adequate dosing and duration of fluconazole during the initial treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Rhodotorula mucilaginosa is an emerging pathogen with a high resistance profile and the mortality rate has been reported around 10% with the complications of sepsis, shock and organ dysfunction [2][3][4]. It forms salmon-pink colonies when cultured on standard artificial media -a vital and early clue to its presence in a fungal culture [5]. In order to prevent the risk of treatment failure, it is crucial for a timely clinical assessment in detecting Rhodotorula mucilaginosa infection so that appropriate antifungal therapy can be initiated early [4].…”
Section: Introductionmentioning
confidence: 99%
“…The overall mortality rate was approxi-mately 12% before the pandemic [80]. The diagnosis of this mycosis can be difficult because it is a capsulated yeast and can be confused with several fungal agents; until recently, it was considered nonpathogenic, making it necessary to alert health professionals for a correct diagnosis of rhodotorulosis [86].…”
Section: Rhodotorula Mucilaginosamentioning
confidence: 99%